2022
DOI: 10.21273/hortsci16478-21
|View full text |Cite
|
Sign up to set email alerts
|

Flower Forms and Ploidy Levels Impact Fertility in Althea

Abstract: Althea (Hibiscus syriacus) is a popular shrub known for its vibrant summer blooms and winterhardiness; however, althea produces capsules with numerous seeds that germinate and cause a nuisance in production and the home landscape. Breeding for sterile forms has long been a goal of Hibiscus breeders, yet many popular “sterile” cultivars have been reported as weedy. The purpose of this study was to evaluate female and male fertility of tetraploid and hexaploid cultivars, and to evaluate the female fertility of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Thus, we recommend ‘Resi’ as a pollen parent to breed for larger flowers, not only through transgressive segregation but also ploidy manipulation. Breeders wishing to increase flower size using ploidy manipulation can use treatment of somatic material in vitro or in vivo to create octoploids and backcross to yield hexaploids [ 18 ]. However, using ‘Resi’ as a male parent and selecting progeny with large flowers may be a more efficient method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we recommend ‘Resi’ as a pollen parent to breed for larger flowers, not only through transgressive segregation but also ploidy manipulation. Breeders wishing to increase flower size using ploidy manipulation can use treatment of somatic material in vitro or in vivo to create octoploids and backcross to yield hexaploids [ 18 ]. However, using ‘Resi’ as a male parent and selecting progeny with large flowers may be a more efficient method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, various ploidy levels of H. syriacus cultivars or breeding materials of tetraploid, pentaploid, and octoploid have been developed and showed altered morphologies [ 7 , 13 , 16 ]. For example, the hexaploid (2 n = 120) cultivars have a larger flower [ 7 ] and decreased fertility [ 17 ] compared to tetraploid cultivars [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…More than a decade of testing available cultivars, including ploidy analysis and testing seed production (fecundity) through controlled crossing and open pollination in fields, has shown that most cultivars are highly fertile tetraploids (4x), but that hexaploids (6x) such as Pink Giant ('Flogi') had reduced fertility (Lattier and Contreras 2022). The availability of multiple cytotypes presented the opportunity to make interploidy crosses to develop 5x plants with reduced fertility (Lattier and Contreras 2022). Pentaploid (5x) plants yielded 0.8 seed per pollination, whereas 4x plants yielded 10 seeds per pollination (Lattier and Contreras 2022).…”
mentioning
confidence: 99%
“…The availability of multiple cytotypes presented the opportunity to make interploidy crosses to develop 5x plants with reduced fertility (Lattier and Contreras 2022). Pentaploid (5x) plants yielded 0.8 seed per pollination, whereas 4x plants yielded 10 seeds per pollination (Lattier and Contreras 2022). To date, we are unaware of any available cultivars that are 5x.…”
mentioning
confidence: 99%